O lúdico político em Civilization VI - Bergston Luan Santos (2020)
This study sought to contribute to the discussion on ludic in contemporary society mediated by the complexity of digital. In this sense, we start from the premise that ludic is a pertinent element for understanding different human relationships. In this way, in this study we problematize a digital game with a thematic focus on the political actions in the game that are mediated by interaction with Artificial Intelligence. For this, we have a qualitative research that involved description and analysis of the material collected and followed primary sources such as the game itself (Civilization VI), the game manual and internal information such as 'Civilopédia', and we also used secondary sources such as magazines, interviews and several websites specialized in games, this with the objective of creating conditions for dialogue and empirical-methodological triangulation about the object studied. Likewise, we constructed a theoretical discussion that problematized the playfulness element and the political element of politics as components that could be programmed, understanding that this allows the construction of different situations of challenge, conflict and dispute in the game. We still infer that these three situations end up being filled in the game by several digitally programmed references such as, for example, forms of government, which give elements of gameplay in a game that challenges the player to “create an Empire that resists the wear and tear of time”. Therefore, this work collaborates with a discussion pertinent to gamestudies when it seeks to reflect the ludic as a structuring element of digital games and this without giving up the credentials that make up all the complexity that is a digital game.